Farmacoterapia antifúngica sistêmica em um hospital de ensino: Estudo de utilização e segurança - Maria Clara Padovani de Souza (2015)
Invasive fungal diseases are associated with a high rates of morbidity and mortality, particularly for hospitalized patients. Inappropriate use of antifungal agents may result in adverse events, unnecessary exposure, higher costs and increased microbial resistance. The aims of this study were to analyze the profile of systemic antifungal, to verify the adherence to treatment protocols, to determine the frequency of drug interactions and adverse drug reactions (ADRs) and to investigate the factors associated with ADRs with the use of systemic antifungal drugs in patients admitted to a high-complexity hospital. This cross-sectional study involved the investigation of 183 medical records of patients receiving systemic antifungal therapy for more than 24 hours with a length of stay of longer than five days. Antifungal drugs were labeled using the fourth level of the Anatomical Therapeutic Chemical Classification System (ATC). The adherence to treatment protocols was evaluated for indication, dosage and drug interactions. Drug interactions were analyzed using the DRUG-REAX software. ADR causality was classified using the Naranjo algorithm. ADR severity was also evaluated. Data were analyzed with descriptive statistics and univariate analysis and multivariate logistic regression. A total of 183, 105 (57.4%) patients were males. The median age was 43 years. There were 214 episodes of infection identified and were established 320 treatments. Of these treatments, 163 (50.9%) were preemptive, 63 (19.7%) were targets, 56 (17.5%) were empirical and 38 (11.9%) were prophylactic. The systemic antifungal drugs prescribed more frequently were fluconazole 170 (53.1%), followed by voriconazole 43 (13.4%) and amphotericin B deoxycholate 36 (11.3%). The overall adherence to treatment protocol was 29.4%. The adherence of the indication were found to be appropriate in 269 (84.1%). Dosage were found to be appropriate in 217 (67.8%) and significant drug interaction in 151 (47.2%). Approximately 30.0% of patients had at least one ADR involving antifungals. Ninety-six ADRs were detected. Regarding the causality 63 (65.6%) were classified as possible. The majority of the ADRs 87 (90.6%) was of moderate severity. The main ADRs observed were an infusion reaction, hypokalaemia, nephrotoxicity and hepatotoxicity. Amphotericin B and voriconazole were associated with ADRs of major clinical impact. Eleven (11.4%) of the 96 ADRs were related to drug interactions. In the multivariate logistic model the following three factors were independently associated with the occurrence of ADRs caused by antifungal drug use: neoplasm diagnosis, length of hospital stay and the use of 13 drugs. The prevalence of the use of fluconazole and new antifungals were compatible with the clinical characteristics of patients. The antifungal prescribed dosage and the presence of potential drug interactions were determinants of inadequacies in antifungal drug therapy. ADR related drug interactions involving antifungals were infrequent but clinically important. The ADR occurrence in patients receiving antifungal therapy were associated with a diagnosis of cancer, length of hospital stay and number of drugs used concomitantly with antifungals.